ILO Law and the Right to Strike The International Perspective - Servais, Jean-Michel (Canadian Labour & Employment Law Journal, 2009)
The author, former Director of the International Labour Organization, provides a succinct overview of the principles developed by the ILO's supervisory bodies (especially the Committee on Freedom of Association) in relation to the right to strike. The topics discussed include general recognition of the right to strike, as well as the types of conditions and restrictions on collective action that may be permitted, e.g. in the area of essential services. The paper also examines the extent to which public authorities may interfere in strikes, and whether sanctions and anti-strike measures imposed by employers are allowed. In the second part of the paper the author turns to a consideration of the ILO standards that apply to alternative means of dispute resolution, with particular emphasis on the use of conciliation, mediation and arbitration. The paper concludes with some general observations based on the ILO's accumulated experience.